Volleyball players` mental health improvement trainings customized to ovarian menstrual cycle - Baykovsky, Yu. V.; Aleshicheva, A. V.; Samoylov, N. G.; Kazakov, D. A. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to profile the volleyball players` mental health variations versus the ovarian menstrual cycles and offer the ovarian menstrual cycle customized mental health sensitive training system. The ovarian menstrual cycle customized trainings were designed to mitigate the physical and mental stresses in the `problematic` (premenstrual, menstrual and ovular) phases of an ovarian menstrual cycle by the eased reasonably individualized technical and tactical trainings. The trainees` mental statuses were tested under the study by the Gissen`s questionnaire survey to obtain the subjectively rated ailments/ pains, wellbeing, activity, mood and overall mental health rates.